Kształtowanie się efektywności i struktury nakładów w rolnictwie polskim w latach 1960 - 1981 - Matulewicz, Klemens (Wydział Prawa i Administracji UAM, 1983)
The resulto of a study on trends in effectiveness and total inputs in the Polish agriculture of 1960 - 1981 are presented in the article. It could be established on the grounds of the investigations that there was a systematic increase in total inputs observed in the Polish conditions of the forementioned period. A rate of growth in total inputs was much higher in in the small-scale sector of agriculture than in the State agriculture enterprises. As a result of that process a gap between the indices characterizing effectiveness of total inputs in the small-scale sector and the State agricultural enterprises was continuing to widen in favor the nationalized agriculture. Substantial changes of the structure of total inputs could also be observed in the period under examination. There was a decrease in exipenditure of direct labor and rise of capital expenditures. In material expenditures, there was a reduction in a portion of expenditures originating from a production of own make and increase in a portion of external expenditures agricultural and mon- agricultural. The gain in the latter portion could be particularly observed in the State agricultural farms. The external inputs amounted, at the end of examined period, to over 2/3 of total sum of material expenditures incurred by the State agricultural enteeprises, while they accounted for 40% of the expenditures im the small-scale sector of agriculture.
Trends in effectiveness and structure of expenditures in the Polish agriculture of 1960 -1981